1986
DOI: 10.1080/00288233.1986.10430450
|View full text |Cite
|
Sign up to set email alerts
|

The response of simulated swards of perennial ryegrass and white clover to enriched atmospheric C02: Interaction with nitrogen and photosynthetic photon flux density

Abstract: This paper reports the growth response to elevated CO 2 concentration of artificial swards of clover (Trifolium repens L. cv. Grasslands Pitau), ryegrass (Lolium perenne L. cv. Grasslands Ruanui), and mixed clover -ryegrass. The growth rate of the swards was varied by changing nitrogen nutrition and photosynthetic photon flux density (PPFD). We examined whether the response to elevated CO 2 was the same in a dense, established sward as previously reported for isolated plants. Artificial swards of clover and ry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2

Year Published

1991
1991
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 18 publications
1
13
2
Order By: Relevance
“…At subsequent cuts a response of clover to CO 2 was not evident, whereas ryegrass showed increasing gains in productivity until the final regrowth period. These results are in contrast to those recorded by Hardacre et al (1986). In their mini-swards, with defoliation, clover growth was more strongly enhanced by CO 2 than ryegrass growth.…”
Section: Competitive Relationshipscontrasting
confidence: 56%
See 3 more Smart Citations
“…At subsequent cuts a response of clover to CO 2 was not evident, whereas ryegrass showed increasing gains in productivity until the final regrowth period. These results are in contrast to those recorded by Hardacre et al (1986). In their mini-swards, with defoliation, clover growth was more strongly enhanced by CO 2 than ryegrass growth.…”
Section: Competitive Relationshipscontrasting
confidence: 56%
“…The response to CO 2 is generally stronger at higher Photon Flux Densities (PPFDs). An exception appears to be the response of ryegrass in the experiment of Hardacre et al (1986), which was found to have a stronger enhancement of growth rate at the lower PPFD. However, the "high" PPFD treatment in this experiment was only 460 ~ mol!…”
Section: Interactions With Other Environmental Factorsmentioning
confidence: 94%
See 2 more Smart Citations
“…In a recently established mixed sward on an artificial medium, elevated CO2 markedly stimulated the growth of ryegrass and white clover (Hardacre et al, 1986). In contrast, elevated CO2 had a comparatively small effect on plant yields in our older pasture communities, and then mainly at the higher temperatures.…”
Section: Discussionmentioning
confidence: 93%